Synthesis of copper nanoparticles in presence of surfactants and evaluation of heat transfer performance of copper nanofluid - Kapadnis, Chetan V.; Gundeli, Kartik P.; Saini, Daulat R.; Bhatkhande, Dhananjay S. (Journal of Nanofluids, 2017)
Copper nanoparticles were synthesized by reduction of copper nitrate hexahydrate using glucose as a green reducing agent. Effect of various synthesis parameters such as the amount of reducing agent, type of surfactant, the concentration of surfactant on particle size and morphology has been studied. Particles thus synthesized were characterized using analytical tools like X-ray Diffraction (XRD), Dynamic Light Scattering (DLS) and Scanning Electron Microscopy (SEM). XRD results show copper peaks at 2 angles 43.34, 50.48 and 74.19° corresponding to the planes (111), (200) and (220) respectively and possessing FCC (Face Centred Cubic) crystal lattice and polydispersed particles with crystallite size ranging from 43 to 103 nm. Further Cu nanoparticles were dispersed in water to prepare nanofluid and heat transfer properties such as heat transfer coefficient, viscosity and density were evaluated. Nanofluid models proposed elsewhere were also used for theoretical property evaluations. Nearly 100% increase in heat transfer coefficient was observed at 1% (by volume) particle concentration of copper nanoparticles in water.
Keywords: Chemical Reduction; Copper nanoparticles; green synthesis; Nanofluids; surfactant